A controllable gasification pore-forming method for preparing coal-based porous carbon material by liquid flash explosion and chemical etching synergy, coal-based porous carbon material and application
Patent Information
- Application Number
- CN202611274011.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-16
AI Technical Summary
以上技术方案均采用管式炉煅烧保温的方式制备煤基多孔炭,这种方法存在加热和冷却周期长、反应时间长、能耗高等固有限制
本发明利用升温速率为104K/min的闪蒸焦耳热技术制备煤基多孔炭材料,使得制备周期相较于传统管式炉制备方法缩短90%以上,能耗大幅降低。本发明提出的液体闪蒸爆破及化学刻蚀协同作用制备煤基多孔炭材料的可控气化造孔方法,可以利用液态试剂在焦耳热瞬时升温气化产生的瞬时高压,对煤粉产生物理爆破和化学刻蚀的协同作用,相比传统水蒸气活化需持续通入蒸汽数小时,本发明通过控制液态试剂活化次数,即可精准调控造孔程度,这种次数可控的造孔方式操作简便,避免了传统方法中活化时间、温度、气氛流量等多参数耦合难以精准控制的问题;通过改变液体闪蒸爆破活化与碱闪蒸活化的先后顺序,可定向构筑三种差异化微观形貌:(1)先液体闪蒸活化后碱闪蒸活化:液体闪蒸先打开孔道,碱深度刻蚀形成蜂窝状贯通孔;(2)先碱闪蒸活化后液体闪蒸活化:碱先形成裂隙,液体闪蒸爆破扩孔形成气泡状;(3)一步焦耳热闪蒸活化处理:双重刻蚀协同作用形成气泡孔结构或花状结构。这种顺序可调的调控方式突破了传统单一活化路径的局限,实现了从孔径分布到孔道形貌的全方位精准调控,为不同应用场景提供定制化孔结构。
Smart Images

Figure CN122930739A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coal-based functional material preparation technology, specifically to a controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash evaporation explosion and chemical etching, coal-based porous carbon materials and their applications, and more specifically, to a controllable gasification pore-forming method for preparing coal-based porous carbon by the synergistic effect of liquid flash evaporation explosion and chemical etching, and the application of the prepared porous carbon materials in supercapacitor electrode materials. Background Technology
[0002] To address the environmental and energy crisis caused by the overconsumption of fossil fuels, developing efficient energy storage technologies to overcome the intermittent nature of renewable energy has become crucial for building a new energy system. Among these technologies, porous carbon, with its high specific surface area, excellent chemical stability and conductivity, and low cost, has become the most widely used electrode material for supercapacitors in current industrial applications. Coal, as a geologically abundant, economically accessible, and geostrategically significant natural resource, has become the most directly accessible precursor for porous carbon. Transforming coal from a fuel into a raw material to produce high-value-added derived carbon materials is key to its transformation from an energy source to a cleaner and more material-oriented industry.
[0003] Currently, the mainstream methods for preparing porous carbon mainly include pyrolysis activation (physical activation, chemical activation), hydrothermal carbonization, and chemical vapor deposition. These methods often suffer from inherent limitations such as long heating and cooling cycles, long reaction times, high energy consumption, and cumbersome pre- and post-synthesis steps like separation, purification, and drying. For example, in the field of coal-based porous carbon preparation, patent CN116282014A discloses a method for preparing coal-based porous carbon materials and their applications, where high-temperature activation is achieved through calcination at 600-1200℃ for 2-6 hours in an argon atmosphere. Patent CN118343755A discloses a method for preparing coal-based carbon materials for sodium-ion battery anodes, where coal-based porous carbon obtained by calcination at 700-900℃ for 1-3 hours in a tubular furnace is mixed with tetrahydrofuran-soluble coal liquefaction pitch to obtain the coal-based carbon material for sodium-ion battery anodes. Both of these technical solutions employ tubular furnace calcination and heat preservation to prepare coal-based porous carbon, which suffers from inherent limitations such as long heating and cooling cycles, long reaction times, and high energy consumption. Summary of the Invention
[0004] The purpose of this invention is to overcome the inherent limitations of traditional porous carbon preparation methods, such as long heating and cooling cycles, long reaction times, high energy consumption, and cumbersome pre- and post-synthesis steps like separation, purification, and drying. This invention provides a controllable gasification pore-forming method for preparing coal-based porous carbon materials through the synergistic effect of liquid flash explosion and chemical etching, along with the coal-based porous carbon materials and their applications. Using abundant low-rank coal as raw material and combining Joule heating technology, this invention proposes a controllable gasification pore-forming method strategy for preparing coal-based porous carbon materials through the synergistic effect of liquid flash explosion and chemical etching. This method utilizes the ultrafast heating characteristics of Joule heating (heating rate can reach 10... 4 The pressure (K / min) causes the liquid reagents adsorbed inside or on the surface of the coal matrix to be vaporized instantaneously, generating high pressure. This produces a synergistic effect of physical explosion and chemical etching on the carbon skeleton. At the same time, the pore morphology can be directionally controlled by adjusting the order of activation steps, and the pore size can be quantitatively controlled by adjusting the number of activations.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows: A controllable gasification pore-forming method for preparing coal-based porous carbon materials by synergistic effects of liquid flash evaporation explosion and chemical etching, the method comprising raw material pretreatment, flash evaporation activation treatment and post-treatment; In the raw material pretreatment, the coal sample to be treated is ball-milled and sieved to obtain coal powder; The flash activation treatment is selected from any of the following methods: (A) Perform at least one liquid flash evaporation activation pore-forming treatment, followed by one alkaline flash evaporation activation etching treatment; or, (B) Perform an alkaline flash evaporation activation etching process first, followed by at least one liquid flash evaporation activation pore-forming process; or, (C) One-step Joule heat flash activation treatment; In the liquid flash evaporation activation pore-forming process, the material to be activated is mixed with a liquid reagent and stirred until a paste-like mixture is formed. This paste-like mixture is then wrapped in graphite paper, connected to a DC power supply, and placed in a Joule thermal shock apparatus. Under a protective atmosphere, the mixture is heated at a rate of 10°C. 4 K / min for short-term thermal shock treatment; In the alkaline flash activation etching process, the material to be activated is mixed with an aqueous solution containing an alkaline reagent and impregnated. After drying, an impregnating material is obtained. The impregnating material is then wrapped in graphite paper, connected to a DC power supply, and placed in a Joule thermal shock apparatus. Under a protective atmosphere, the temperature is increased at a rate of 10°C. 4 K / min for short-term thermal shock treatment; In the Joule heat flash activation process, the coal powder, alkaline activator, and deionized water are mixed and stirred until a paste-like mixture is formed. This paste-like mixture is then wrapped in graphite paper, connected to a DC power supply, and placed in a Joule heat shock device. Under a protective atmosphere, the temperature is increased at a rate of 10°C.4 Joule heat treatment was performed at K / min; The material after flash activation treatment is post-processed to obtain the coal-based porous carbon material.
[0006] Optionally, in the liquid flash evaporation activation pore-forming process, the activation temperature of the short-time thermal shock treatment is 600℃, and the activation time of the short-time thermal shock treatment is 20s.
[0007] Optionally, in the liquid flash evaporation activation pore-forming process, the liquid reagent is deionized water or ammonia.
[0008] Optionally, in the alkaline flash evaporation activation etching process, the mass ratio of the alkaline reagent to the material to be activated is 3:1.
[0009] Optionally, in the alkaline flash evaporation activation etching process, the immersion temperature is room temperature.
[0010] Optionally, in the alkaline flash evaporation activation etching process, the drying temperature is 105°C.
[0011] Optionally, in the alkaline flash evaporation activation etching process, the activation temperature of the short-time thermal shock treatment is 900°C, and the activation time of the short-time thermal shock treatment is 60s.
[0012] Optionally, the alkaline reagent includes potassium hydroxide.
[0013] Optionally, in the step of Joule heat flash activation treatment, the material processing method is to mix the alkaline activator with deionized water to form a solution, and then mix the solution with coal powder and stir until it becomes a paste.
[0014] Optionally, the alkaline activator includes potassium hydroxide.
[0015] Optionally, in the step of Joule heat flash activation treatment, the Joule heat treatment temperature is 900℃; and the Joule heat treatment time is 60s.
[0016] Optionally, in the one-step Joule heat flash activation treatment, the mass ratio of the coal powder to the alkaline activator is 1:1.
[0017] Optionally, the post-processing includes: naturally cooling the flash-activated material to room temperature and then removing it, followed by acid washing to remove acid-soluble impurities, washing with hot distilled water to remove impurities, and drying.
[0018] Optionally, the reagent used for pickling is an HCl solution.
[0019] Optionally, the drying temperature is 105°C; the drying time is 12 hours.
[0020] Optionally, the concentration of the reagent used for pickling is 1.0 mol / L, the pickling temperature is 60℃, and the pickling time is 2 hours.
[0021] Optionally, the number of times the liquid flash evaporation activation pore-forming treatment and the alkaline flash evaporation activation etching treatment are performed can be adjusted independently to achieve quantitative control over the degree of pore formation.
[0022] Optionally, in mode (A), the liquid flash evaporation activation pore-forming treatment is performed 1 to 5 times; the alkaline flash evaporation activation etching treatment is performed once. When prepared using mode (A), the coal-based porous carbon material exhibits a regular honeycomb-like interconnected pore structure, forming a multi-level interconnected pore structure where micropores, mesopores, and macropores coexist. The proportion of composite pores can be quantitatively controlled by adjusting the number of activations, thereby quantitatively controlling the degree of pore formation.
[0023] Optionally, in mode (B), the alkaline flash evaporation activation etching treatment is performed once; the liquid flash evaporation activation pore-forming treatment is performed 1 to 5 times. When prepared using mode (B), the coal-based porous carbon material exhibits a bubble-like porous structure, and the proportion of composite pores can be quantitatively controlled by adjusting the number of liquid flash evaporation activations, thereby quantitatively controlling the degree of pore formation.
[0024] Optionally, in mode (C), the one-step Joule heat flash activation treatment is performed 1 to 3 times. The coal-based porous carbon material exhibits different shapes with increasing activation times. When activated once, the coal-based porous carbon material exhibits an interlinked bubble pore structure. When activated three times, the coal-based porous carbon material exhibits a unique flower-like morphology. The original circular pores gradually thin and break after multiple expansions and bursts. The high-pressure impact of each activation causes slight wrinkles and cracks in the pore walls, and subsequent activations further expand these cracks into branch channels. Similarly, the proportion of composite pores can be quantitatively controlled by adjusting the number of liquid flash activations, thereby quantitatively controlling the degree of pore formation.
[0025] Optionally, in modes (A), (B), and (C), the thickness of the graphite paper is 0.05 mm.
[0026] Optionally, in modes (A), (B), and (C), the protective atmosphere is an argon atmosphere.
[0027] Optionally, the coal sample to be processed is low-rank coal; the low-rank coal is sub-bituminous coal.
[0028] Optionally, the particle size of the pulverized coal is 150-200 mesh.
[0029] Optionally, the material to be activated is pulverized coal in the first treatment and the product of the previous unit in subsequent units.
[0030] The present invention also discloses a coal-based porous carbon material, which is prepared by the above method; the microstructure of the coal-based porous carbon material exhibits at least one of honeycomb-like through-pore structure, bubble-like porous structure and flower-like structure.
[0031] Optionally, the specific surface area of the coal-based porous carbon material is 1800~2700 m². 2 / g.
[0032] Optionally, the coal-based porous carbon material contains oxygen-containing functional groups, and the surface oxygen content is 7-17%.
[0033] This invention mixes a liquid with the carbon material to be porous, distributing the liquid across the surface and / or internal cracks and pores of the carbon material. Joule heating is then applied to induce a rapid temperature increase, causing the liquid to preferentially undergo a flash phase transition and violently expand in volume, while the solid carbon skeleton does not undergo a phase transition or a similar volume change. This creates localized instantaneous high pressure, resulting in the explosion, pore expansion, and pore connectivity of the carbon skeleton. Simultaneously, the liquid, under high temperature conditions, also chemically oxidizes and etches the carbon skeleton, regulating surface functional groups and carbon structure. The method allows for control of pore structure and surface chemical state through the number of flashes, processing sequence, and liquid type, offering advantages such as speed, convenience, and process controllability. Taking coal-based carbon materials as an example, liquid flash explosion activation combined with alkaline flash activation is used. Pretreated coal powder, after different processing modes, can form porous carbon with different pore morphologies, including honeycomb-like interconnected pore structures, bubble-like porous structures, and flower-like structures. Furthermore, by controlling the number of processing cycles, the specific surface area of the resulting porous carbon can be quantitatively controlled, achieving excellent energy storage performance. This invention employs flash Joule heating technology, utilizing a controlled gasification pore-forming method that combines liquid flash explosion and chemical etching to prepare coal-based porous carbon. This application of coal to produce high-value-added porous carbon materials realizes the transformation from fuel to raw material.
[0034] Optionally, the oxygen-containing functional group includes at least one of CO, C=O, and OC=O.
[0035] Optionally, the pore size distribution and microstructure of the coal-based porous carbon material vary with the sequence and number of liquid flash activation and alkali activation processes. When prepared using mode (A), the coal-based porous carbon material exhibits a regular honeycomb-like interconnected pore structure with a specific surface area of 2500~2700 m². 2 / g, with pore sizes distributed in the micropore range of 0.6nm and 0.8nm, the mesopore range of 2.5nm and the macropore range of >100nm, forming a multi-level interconnected pore structure in which micropores, mesopores and macropores coexist.
[0036] Optionally, when prepared using mode (B), the coal-based porous carbon material exhibits a bubble-like porous structure with numerous nanoscale cracks distributed along the edges of the bubble pores, and a specific surface area of 1800~2000 m². 2 / g, the pore size distribution is mainly micropores with a small amount of mesopores.
[0037] Optionally, when prepared using mode (C), the coal-based porous carbon material exhibits a bubble-like porous structure or a flower-like structure, with a surface rich in micropores and a specific surface area of 2100~2300 m². 2 / g, with pore size distribution concentrated in the micropore range below 2nm.
[0038] The present invention also discloses a coal-based porous carbon material prepared by the method described above, or the application of the coal-based porous carbon material described above in supercapacitor electrode materials.
[0039] Optionally, the coal-based porous carbon material is mixed with a conductive agent and a binder at a mass ratio of 8:1:1 to prepare an electrode slurry, which is then coated onto a current collector to prepare a supercapacitor electrode sheet. The electrode sheet is then assembled into a symmetrical supercapacitor. The supercapacitor exhibits excellent electrochemical performance in a 6 mol / L KOH aqueous electrolyte, with a specific capacitance ≥212 F / g at a current density of 0.5 A / g. The energy density is ≥22.7 Wh / kg at a power density of 496~499 W / kg, and the capacity retention rate is ≥92% and the coulombic efficiency is ≥99.5% after 10,000 charge-discharge cycles.
[0040] Optionally, the symmetrical supercapacitor in a 6 mol / L KOH aqueous electrolyte has a specific capacitance of 212-308 F / g at a current density of 0.5 A / g; an energy density of 22.7-29.3 Wh / kg at a power density of 496-499 W / kg; and a capacity retention of ≥92.75% after 10,000 charge-discharge cycles.
[0041] Optionally, the conductive agent is conductive carbon black.
[0042] Optionally, the adhesive is polytetrafluoroethylene.
[0043] Optionally, the current collector is nickel foam.
[0044] Implementing the embodiments of the present invention will have the following beneficial effects: This invention utilizes a heating rate of 10 4The flash joule heating technology at K / min for preparing coal-based porous carbon materials reduces the preparation cycle by more than 90% compared to traditional tubular furnace methods, and significantly reduces energy consumption. The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash evaporation explosion and chemical etching proposed in this invention can utilize the instantaneous high pressure generated by the instantaneous heating and gasification of liquid reagents in Joule heating to produce a synergistic effect of physical explosion and chemical etching on coal powder. Compared with the traditional steam activation which requires continuous steam supply for several hours, this invention can precisely control the degree of pore-forming by controlling the number of activations of liquid reagents. This pore-forming method with controllable number of activations is easy to operate and avoids the problem of difficulty in accurately controlling multiple parameters such as activation time, temperature, and atmosphere flow rate in traditional methods. By changing the order of liquid flash evaporation explosion activation and alkali flash evaporation activation, three different micromorphologies can be constructed in a directional manner: (1) Liquid flash evaporation activation followed by alkali flash evaporation activation: Liquid flash evaporation opens the channels first, and alkali deep etching forms honeycomb-shaped through holes; (2) Alkali flash evaporation activation followed by liquid flash evaporation activation: Alkali first forms cracks, and liquid flash evaporation explosion expands the holes to form bubble-like structures; (3) One-step Joule heating flash evaporation activation treatment: The dual etching synergistic effect forms bubble-like structures or flower-like structures. This sequentially adjustable control method breaks through the limitations of the traditional single activation path, realizing comprehensive and precise control from pore size distribution to pore morphology, and providing customized pore structures for different application scenarios. Attached Figure Description
[0045] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0046] Figure 1 The flowcharts for the liquid flash activation step, the alkaline flash activation step, the acid washing and drying step, and the liquid flash explosion principle diagram are shown in the embodiments of the present invention.
[0047] Figure 2 (a) is an electron microscope image of the pore features after liquid flash activation once and then alkaline flash activation in an embodiment of the present invention; (b) is an electron microscope image of the pore features after liquid flash activation three times and then alkaline flash activation in an embodiment of the present invention; (c) is an electron microscope image of the pore features after liquid flash activation five times and then alkaline flash activation in an embodiment of the present invention; (d) is an electron microscope image of the pore features after liquid flash activation seven times and then alkaline flash activation in an embodiment of the present invention.
[0048] Figure 3(a) is an electron microscope image of the pore features after alkaline flash activation followed by liquid flash activation in an embodiment of the present invention; (b) is an electron microscope image of the pore features after alkaline flash activation followed by three liquid flash activations in an embodiment of the present invention; (c) is an electron microscope image of the pore features after alkaline flash activation followed by five liquid flash activations in an embodiment of the present invention; (d) is an electron microscope image of the pore features after alkaline flash activation followed by seven liquid flash activations in an embodiment of the present invention.
[0049] Figure 4 (a) is an electron microscope image of the pore features of a coal powder sample after one activation by mixing liquid water and alkali simultaneously in an embodiment of the present invention; (b) is an electron microscope image of the pore features of a coal powder sample after three activations by mixing liquid water and alkali simultaneously in an embodiment of the present invention; (c) is an electron microscope image of the pore features of a coal powder sample after four activations by mixing liquid water and alkali simultaneously in an embodiment of the present invention.
[0050] Figure 5 The images shown are electron micrographs of the pore features obtained by mixing ammonia water and coal powder samples and activating them five times in an embodiment of the present invention.
[0051] Figure 6 The images show the cyclic voltammetry (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon used to prepare supercapacitor electrode materials in the embodiment of this invention, obtained by liquid flash activation followed by alkaline flash activation.
[0052] Figure 7 The cyclic voltammetric (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by initial alkaline flash activation followed by liquid flash activation are shown in the embodiments of the present invention for the preparation of supercapacitor electrode materials.
[0053] Figure 8 The cyclic voltammetric (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by the alkaline-water co-activation mode in the embodiments of the present invention are shown.
[0054] Figure 9 The cyclic voltammetric (CV) and constant current charge-discharge (GCD) curves of the coal-based porous carbon obtained by five ammonia activations in this embodiment of the invention are shown. Detailed Implementation
[0055] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0056] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0057] This invention proposes a controllable gasification pore-forming method for preparing coal-based porous carbon materials based on Joule heating technology, utilizing the synergistic effects of liquid flash explosion and chemical etching. This method promotes deep mixing of the activator and raw materials, enhancing the activation effect. By simply changing the addition method of the liquid reagent and the number of activation cycles, the morphological characteristics of the porous carbon can be differentiated and controlled, providing a simple and efficient new path for the directional structural design of porous carbon. Transforming coal from fuel to raw material is crucial for its transition from energy to clean utilization and materialization. This invention provides a feasible path for preparing high-value-added porous carbon materials from coal.
[0058] like Figure 1 The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash evaporation explosion and chemical etching includes: a raw material pretreatment step, a flash evaporation activation treatment step, and a post-treatment step.
[0059] The flash activation process is selected from any of the following schemes: (A) performing at least one liquid flash activation pore-forming process followed by one alkaline flash activation etching process; or, (B) performing one alkaline flash activation etching process followed by at least one liquid flash activation pore-forming process; or, (C) performing a one-step Joule heat flash activation process; in schemes (A), (B), and (C), the thickness of the graphite paper is 0.05 mm.
[0060] The specific implementation method is as follows: Raw material pretreatment steps: In this example, Zhundong sub-bituminous coal from the Wucaiwan mining area in Zhundong, Xinjiang was selected as the base sample after ball milling and sieving, with a particle size range of 150-200 mesh. Industrial analysis of raw coal: moisture 9.63 wt%, ash 5.50 wt%, volatile matter 40.30 wt%, fixed carbon 44.57 wt%. Elemental analysis (dry ash-free basis): C 61.40%, H 4.41%, O 17.69%, N 0.89%, S 0.48%.
[0061] Liquid flash evaporation activation pore-forming step: Weigh an appropriate amount of coal powder and mix it with a small amount of deionized water to form a paste. Transfer the paste onto a graphite paper substrate and wrap it. Connect the graphite paper to a DC power supply in a high-temperature Joule thermal shock (JH) device. Set the heating time to 20 s and the heating rate to 10. 4 K / min, subjected to short-term thermal shock at 600℃ in an argon atmosphere.
[0062] Alkali flash evaporation activation etching procedure: Take the product obtained from liquid flash evaporation activation, weigh a certain amount of KOH according to a KOH to product mass ratio of 3:1, and dissolve it in a small amount of deionized water. Add the product to the above solution and impregnate at room temperature. After thorough stirring, place it in a 105℃ electric oven to evaporate to dryness. After impregnation and drying, transfer the sample back to graphite paper, wrap it, and connect it to a high-temperature Joule thermal shock (JH) apparatus with a DC power supply. Under an argon atmosphere, perform annealing for 60 seconds at an activation temperature of 900℃ and a heating rate of 10. 4 K / min.
[0063] One-step Joule heat flash activation treatment: First, weigh 100 mg of coal powder. Weigh a certain amount of KOH according to a KOH-to-coal powder mass ratio of 1:1. Mix the coal powder, KOH, and deionized water to form a paste. Transfer the paste onto a graphite paper substrate and wrap it. Connect the graphite paper to a DC power supply in a high-temperature Joule heat shock (JH) apparatus. Under an argon atmosphere, the heating rate is 10°C. 4 The heating rate was set to K / min, and the heating time was set to 60 s. The Joule thermal shock at 900℃ was carried out in an argon atmosphere.
[0064] Acid washing and drying steps: After the product obtained by liquid flash activation and alkaline flash activation is naturally cooled to room temperature, it is taken out and placed in 1.0 mol / L HCl and soaked at 60℃ for 2h to remove acid-soluble impurities. After washing with hot distilled water to remove impurities, it is dried in a hot air drying oven at 105℃ for 12h to obtain coal-based porous carbon material.
[0065] The above-mentioned liquid flash evaporation activation pore-forming step and alkaline flash evaporation activation etching step have multiple implementation methods. The number of liquid flash evaporation activation pore-forming treatments and alkaline flash evaporation activation etching treatments can be adjusted independently to achieve quantitative control of the pore-forming degree.
[0066] Specific Implementation Scheme 1: In Mode (A), this implementation method involves performing a liquid flash evaporation activation pore-forming treatment followed by an alkaline flash evaporation activation etching treatment. For example... Figure 2 As shown in (a), the surface roughness of the obtained coal matrix is significantly improved. Under ultra-fast heating conditions, the etching effect of liquid water effectively breaks the dense surface structure of the raw coal. A large number of uniformly distributed micropores and microcracks are generated on the sample surface, providing initial diffusion channels and active sites for subsequent activation reactions.
[0067] Specific Implementation Scheme Two: In Mode (A), this implementation method involves three liquid flash evaporation activation pore-forming treatments followed by one alkaline flash evaporation activation etching treatment. For example... Figure 2 As shown in (b), under the continuous enhancement of the etching effect of liquid water on the carbon matrix, the original micropores on the obtained porous carbon are continuously etched and expanded, the pore size increases and the pore depth increases.
[0068] Specific Implementation Scheme Three: In Mode (A), this implementation involves five liquid flash evaporation activation pore-forming treatments followed by one alkaline flash evaporation activation etching treatment. For example... Figure 2 As shown in (c), the etching effect of liquid water on the carbon matrix reaches its peak. Existing micropores on the surface are continuously etched and expanded, with increased pore size and depth. Simultaneously, new pores are continuously generated and cross-linked, thus penetrating the entire coal matrix, ultimately forming a continuous, interconnected, and well-developed honeycomb network of channels. This lays the structural foundation for the mass transfer and application performance of porous carbon. The obtained porous carbon sample has a specific surface area of 2655.34 m². 2 The concentration of carbon in the liquid flash evaporation activated carbon ( / g) is significantly higher than that of pure Joule-heated samples and traditional tube furnace activated samples, directly demonstrating that the introduction of liquid flash activation can further enhance the etching effect of the Joule-heated process, greatly increasing the total pore volume and specific surface area of the porous carbon and constructing a more developed pore network. Simultaneously, although a slight isothermal hysteresis loop is present, it indicates that the material is predominantly open-pore with excellent pore connectivity, ensuring sufficient charge storage sites and providing structural support for the rapid transport of electrolyte ions.
[0069] However, a higher number of activations is not necessarily better, such as... Figure 2 As shown in (d), if the number of activations is further increased to seven times and then an alkaline flash evaporation activation etching process is performed, the continuous and intense etching will break through the structural bearing limit of the carbon skeleton itself, severely damage the structural integrity of the carbon matrix, and cause the porous carbon to collapse and break down as a whole. It may even cause the already formed channels to become blocked and the pore structure to deteriorate, which will have a negative impact on the microstructure and subsequent application performance of the material.
[0070] Sample (A) represents a material that has undergone five liquid flash activations followed by one KOH flash activation. The resulting material exhibits a regular honeycomb-like interconnected pore structure with a specific surface area of 2655.34 m² / g. Characteristic peaks appear in the 0.6 nm and 0.8 nm micropore regions, the 2.5 nm mesopore region, and the >100 nm macropore region, forming a multi-level interconnected pore structure. The surface oxygen content of this five-activation sample is 9.85%.
[0071] Figure 6 The results show that the CV curve of the (A) sample remains approximately rectangular under moderate activation cycles. The sample activated by 5 liquid flash evaporation cycles exhibits a more pronounced redox response, indicating a synergistic effect between the double-layer capacitance and the pseudocapacitance contributed by oxygen-containing functional groups. Its specific capacitance in a three-electrode system at 0.5 A / g is 307.77 F / g; after 7 cycles, excessive etching of the pore structure leads to a decrease in capacitance to 214.45 F / g.
[0072] Specific Implementation Scheme Four: In Mode (B), this implementation method involves first performing an alkaline flash evaporation activation etching process, followed by a liquid flash evaporation activation pore-forming process. For example... Figure 3 As shown in (a), the obtained porous carbon surface forms irregular crack-like pores under the strong chemical etching of KOH. Then, because liquid water can fully penetrate into the cracks and original pores generated by KOH pre-etching, under the intense heating conditions of Joule heating, the liquid water in the pores instantly vaporizes and explodes. The high temperature and high pressure gas expands rapidly and breaks through the surrounding carbon matrix, eventually forming characteristic bubble-like pores.
[0073] Specific Implementation Scheme Five: In Mode (B), this implementation method involves first performing an alkaline flash evaporation activation etching process, followed by three liquid flash evaporation activation pore-forming processes. For example... Figure 3 As shown in (b), with the increase of activation times, the cumulative effect of multiple instantaneous high-pressure gasifications will drive the continuous expansion and interconnection of bubble pores, increasing the specific surface area of porous carbon.
[0074] Specific Implementation Scheme Six: In Mode (B), this implementation method involves first performing an alkaline flash evaporation activation etching process, followed by five liquid flash evaporation activation pore-forming processes. For example... Figure 3 As shown in (c), with the increase of activation times, the cumulative effect of multiple instantaneous high-pressure vaporization will drive the bubble pores to continue to expand and interconnect, and some pore walls will break due to repeated high-pressure impact and chemical etching.
[0075] However, a higher number of activations is not necessarily better, such as... Figure 3As shown in (d), when alkaline flash evaporation activation etching is performed once, followed by seven liquid flash evaporation activation pore-forming treatments, the structural bearing capacity of the carbon matrix is exceeded. Excessive pore expansion and pore wall breakage will gradually spread to the entire sample, eventually causing the coal block to break as a whole and destroying the structural integrity of the material.
[0076] Sample (B) represents a material that undergoes one KOH flash activation followed by one liquid flash activation. The resulting material exhibits a bubble-like porous structure with nanoscale cracks distributed along the pore wall edges. The specific surface area is 1904.68 m² / g. The pore size is predominantly micropores, with a distinct peak at 0.6–0.8 nm, a strong peak at approximately 2 nm, and a weak macropore peak at >100 nm. The surface oxygen content of this sample is 13.38%.
[0077] Figure 7 The results show that KOH activation followed by liquid flash evaporation activation improves the symmetry and reversibility of the GCD curve. The mass specific capacitance of the sample after one liquid flash evaporation activation in a three-electrode system is 236.13 F / g, and it remains at 203.96 F / g at 20 A / g. As the rate retention e continues to increase with the number of water activations, the pseudocapacitive peak weakens, and the overall capacitance decreases.
[0078] Specific Implementation Scheme Seven: In Mode (C), this implementation involves simultaneously mixing liquid water and alkali with the pulverized coal sample for a one-step Joule thermal flash activation treatment. For example... Figure 4 As shown in (a), the pore structure on the obtained porous carbon surface is mainly composed of interlinked circular pores, which are generated by the synergistic effect of the instantaneous high pressure generated by the vaporization of liquid water and the chemical etching of KOH.
[0079] Specific Implementation Scheme Eight: In Mode (C), this implementation method involves simultaneously mixing liquid water and alkali with the pulverized coal sample and performing three one-step Joule thermal flash activation treatments. For example... Figure 4 As shown in (b), due to the "etching-expansion-stress release" cycle in the multiple co-activation processes, the high-pressure impact of each activation causes slight wrinkles and cracks in the pore walls. Subsequent activation further expands these cracks into branch channels, resulting in a significant evolution of the porous carbon pore structure, forming a unique flower-like morphology. The original circular pores gradually thin and break after multiple expansions and bursts. The overall structure exhibits a very three-dimensional and interconnected structure, providing abundant active sites for charge storage.
[0080] However, a higher number of activations is not necessarily better, such as... Figure 4As shown in (c), if the number of activations is increased by four more times, the integrity of the flower-like structure is gradually destroyed: the accumulated high pressure impact and excessive chemical etching exceed the structural bearing limit of the carbon skeleton, causing the pore walls to fracture and collapse, and the originally connected multi-level pore network to gradually fragment; as the number of activations further increases, the fragmentation phenomenon continues to intensify, eventually leading to the complete fragmentation of the entire carbon matrix structure and the disappearance of some pores, which reduces the specific surface area and structural stability of the material, and is not conducive to improving the electrochemical energy storage performance.
[0081] Sample (C) represents a material that has undergone three Joule heat flash activation treatments. The resulting material exhibits a flower-like porous structure with a specific surface area of 2191.18 m² / g. The pore volume is concentrated below 2 nm, with characteristic peaks at 0.8 nm and 1.5 nm. Among the samples with different co-activation cycles, the sample treated twice has the highest surface oxygen content, at 16.64%.
[0082] Figure 8 The results showed that the KOH-water co-activated samples generally exhibited good quasi-rectangular CV curves and nearly symmetrical GCD curves. Among them, the three-time co-activated samples had the best performance, with a specific capacitance of 265.53 F / g at 0.5 A / g and 218.64 F / g at 20 A / g, and a rate retention rate of 82.34%. The performance decreased after the fourth co-activation due to structural deterioration.
[0083] Specific Implementation Scheme Nine: In this implementation scheme, the liquid flash activation step involves five activations with ammonia water, followed by one KOH flash activation and etching step according to the above-mentioned alkaline flash activation step, with a KOH to product mass ratio of 3:1. The activation temperature is 900℃ and the time is 60s. Figure 5 As shown, the obtained porous carbon also exhibits a honeycomb-like through-pore structure, but the surface is more fragmented, further increasing the roughness of the pore walls and the complexity of the structure. When the observation scale is further magnified to 500 nm, it is also possible to visually observe that a large number of nanoscale microcracks are uniformly distributed on the pore walls. These secondary nanocracks, which are attached to the main pore walls, are interconnected with the main pore channels and together constitute a multi-level porous structure system.
[0084] Figure 9 The results showed that the sample activated with ammonia water five times had the largest CV curve integral area and GCD discharge time, and the mass specific capacitance was 311.34 F / g in a three-electrode system at 0.5 A / g. Compared with the pure water system, the performance degradation of the ammonia water system after multiple activations was slower, which may be related to the surface chemical regulation of N and O dual elements.
[0085] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A controllable gasification pore-forming method for preparing coal-based porous carbon materials through the synergistic effect of liquid flash evaporation explosion and chemical etching, characterized in that, The method includes raw material pretreatment, flash activation treatment and post-treatment; In the raw material pretreatment, the coal sample to be treated is ball-milled and sieved to obtain coal powder; The flash activation treatment is selected from any of the following methods: (A) Perform at least one liquid flash evaporation activation pore-forming treatment, followed by one alkaline flash evaporation activation etching treatment; or, (B) Perform an alkaline flash evaporation activation etching process first, followed by at least one liquid flash evaporation activation pore-forming process; or, (C) One-step Joule heat flash activation treatment; In the liquid flash evaporation activation pore-forming process, the material to be activated is mixed with a liquid reagent and stirred until a paste-like mixture is formed. This paste-like mixture is then wrapped in graphite paper, connected to a DC power supply, and placed in a Joule thermal shock apparatus. Under a protective atmosphere, the mixture is heated at a rate of 10°C. 4 K / min for short-term thermal shock treatment; In the alkaline flash activation etching process, the material to be activated is mixed with an aqueous solution containing an alkaline reagent and impregnated. After drying, an impregnating material is obtained. The impregnating material is then wrapped in graphite paper, connected to a DC power supply, and placed in a Joule thermal shock apparatus. Under a protective atmosphere, the temperature is increased at a rate of 10°C. 4 K / min for short-term thermal shock treatment; In the Joule heat flash activation process, the coal powder, alkaline activator, and deionized water are mixed and stirred until a paste-like mixture is formed. This paste-like mixture is then wrapped in graphite paper, connected to a DC power supply, and placed in a Joule heat shock device. Under a protective atmosphere, the temperature is increased at a rate of 10°C. 4 Joule heat treatment was performed at K / min; The material after flash activation treatment is post-processed to obtain the coal-based porous carbon material.
2. The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash explosion and chemical etching according to claim 1, characterized in that, In the liquid flash evaporation activation pore-forming process, the activation temperature of the short-time thermal shock treatment is 600℃, and the activation time of the short-time thermal shock treatment is 20s; the liquid reagent is deionized water or ammonia water.
3. The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash explosion and chemical etching according to claim 1, characterized in that, In the alkaline flash evaporation activation etching process, the mass ratio of the alkaline reagent to the material to be activated is 3:1; the immersion temperature is room temperature; and the drying temperature is 105°C. In the alkaline flash evaporation activation etching process, the activation temperature of the short-time thermal shock treatment is 900℃, and the activation time of the short-time thermal shock treatment is 60s. The alkaline reagent is potassium hydroxide.
4. The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash explosion and chemical etching according to claim 1, characterized in that, In the Joule heat flash activation process, the material processing method is to mix the alkaline activator with deionized water to form a solution, and then mix the solution with coal powder and stir until it becomes a paste; the mass ratio of the coal powder to the alkaline activator is 1:
1. The alkaline activator includes potassium hydroxide; In the Joule heat flash activation process, the Joule heat treatment temperature is 900℃ and the Joule heat treatment time is 60s.
5. The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash explosion and chemical etching according to claim 1, characterized in that, The post-processing includes: naturally cooling the flash-activated material to room temperature and then taking it out, followed by acid washing, water washing and drying; The pickling agent used is an HCl solution; The drying temperature is 105℃; the drying time is 12 hours. The concentration of the reagent used for pickling is 1.0 mol / L, the pickling temperature is 60℃, and the pickling time is 2 hours.
6. The controllable gasification pore-forming method for preparing coal-based porous carbon materials by the synergistic effect of liquid flash explosion and chemical etching according to claim 1, characterized in that, The number of times the liquid flash evaporation activation pore-forming treatment and the alkaline flash evaporation activation etching treatment are independently adjustable; In mode (A), the liquid flash evaporation activation pore-forming treatment is performed 1 to 5 times; the alkaline flash evaporation activation etching treatment is performed once. In mode (B), the alkaline flash evaporation activation etching process is performed once; The liquid flash evaporation activation pore-forming treatment is repeated 1 to 5 times; In mode (C), the one-step Joule heat flash activation treatment is performed 1 to 3 times; In patterns (A), (B), and (C), the thickness of the graphite paper is 0.05 mm; In modes (A), (B), and (C), the protective atmosphere is an argon atmosphere; The coal sample to be processed is low-rank coal; the low-rank coal is sub-bituminous coal. The particle size of the pulverized coal is 150-200 mesh.
7. A coal-based porous carbon material, characterized in that, Prepared by the method according to any one of claims 1-6; The microstructure of the coal-based porous carbon material exhibits at least one of the following: honeycomb-like through-pore structure, bubble-like porous structure, and flower-like structure.
8. The coal-based porous carbon material according to claim 7, characterized in that, The specific surface area of the coal-based porous carbon material is 1800~2700 m². 2 / g; The coal-based porous carbon material contains oxygen-containing functional groups, including at least one of CO, C=O and OC=O; the surface oxygen content is 7-17%.
9. The coal-based porous carbon material according to claim 7, characterized in that, When prepared using mode (A), the coal-based porous carbon material exhibits a regular honeycomb-like interconnected pore structure with a specific surface area of 2500~2700 m². 2 / g, with pore sizes distributed in the micropore range of 0.6nm and 0.8nm, the mesopore range of 2.5nm and the macropore range of >100nm, forming a multi-level interconnected pore structure in which micropores, mesopores and macropores coexist; When prepared using mode (B), the coal-based porous carbon material exhibits a bubble-like porous structure with numerous nanoscale cracks distributed along the edges of the bubble pores, and a specific surface area of 1800~2000 m². 2 / g, the pore size distribution is mainly micropores with a small amount of mesopores; When prepared using mode (C), the coal-based porous carbon material exhibits a bubble-like porous structure or a flower-like structure, with a surface rich in micropores and a specific surface area of 2100~2300 m². 2 / g, with pore size distribution concentrated in the micropore range below 2nm.
10. A coal-based porous carbon material prepared by the method of any one of claims 1-6, or the application of the coal-based porous carbon material of any one of claims 7-9 in supercapacitor electrode materials.